Low-grade variants of triple-negative breast carcinoma (TNBC): a review. Issue 2 (February 2020) - Ginter, Paula S.; Fu, Zhiyan; Shin, Sandra J.
Abstract: Low-grade triple negative breast carcinoma (TNBC) differ from conventional type TNBC in clinical, histologic, immunophenotypic, and molecular features. Salient features of low-grade variants of TNBC including adenoid cystic carcinoma (AdCC), secretory carcinoma, low-grade adenosquamous carcinoma (LGASC) and acinic cell carcinoma (ACC), will be discussed, including those useful in distinguishing these unique entities from more commonly encountered differential diagnoses.